Clinical Epidemiology of Head Injury from Road-Traffic Trauma in a Developing Country in the Current Era - Adeleye, Amos O.; Ogun, Millicent I. (Frontiers in Neurology, 2017)
Objectives. Africa and other Asian low-middle income countries(LMIC) account for the greatest burden of the global road traffic injury(RTI)-related head injury(HI). This study set out to describe the incidence, causation and severity of RTI-related HI and associated injuries in a Nigerian academic neurosurgical practice Methods. This is a retrospective cross-sectional analysissurvey of RTI-related HI from a prospective HI registry in an academic neurosurgery practice in Nigeria. Results. All-terrain RTI accounted for 80.6%(833/1034) of HI over an the 7-year study period. All age groups were involved, mean 33.06y(SD 18.30), mode 21-30, 231/833 (27.7%).The male:female ratio was 631:202, ≈3:1. The road trauma occurred exclusively from motorcycle-and motor-vehicle crash (MCC/MVC), MCC caused 56.8%(473/833) of these; the victims were vulnerable road users in 74%, and >90% belong in the low socioeconomic class. Using the Glasgow Coma Scale (GCS)GCS grading, the HI was moderate/severe in 52%; loss of consciousness occurred in 93%, the Abbreviated Injury Severity-head >3 in 74%, and CT Rotterdam score >3 in 52%. Significant extracranial injuries occurred in many organ systems, 421/833(50.5%) having Injury Severity Score(ISS) >25. Surgical lesions included extensive brain contusions in 157(18.8%); acute extradural haematoma in 34(4.1%); acute subdural haematoma in 32(3.8%); and traumatic intracerebral haemorrhage in 27(3.2%) but only 97(11.6%) received operative care for various logistic reasons. The in-hospital outcome was good in 71.3% and poor in 28.7%; the statistically significant, (p< 0.001), determinants of this outcome profile were the severity of the HI, the CT-Rotterdam score, and the ISS. Conclusions. In this study from Nigeria, RTI-related HI emanates from significant trauma to vulnerable road users, and are caused exclusively by motorcycles and motor-vehicles.